Automatic parsing of ball-sports video sequences and its application to soccer - Lim, Teck Sin. (2010)
This thesis describes the study, proposal and design of a video model using a priori knowledge to parse generic ball-sports video sequences and automatically classify them into proper play categories based on their contextual information. An automatic video parser has been implemented using the proposed video model on a specific ball-sports game - soccer. Extensive experimental results showed that our proposed video model is effective. Tests on 720 soccer video clips of 18 play categories have a recognition rate of 87.7%.